Uji Efek Analgesik Ekstrak Etanol Daun Matoa (Pometia pinnata J.R. Forst & G. Forst) pada Mencit Putih (Mus musculus) Jantan - Irma santi; Bayu Putra; Fitka Ulfa Rahman (Journal Borneo, 2023)
Pain is a condition that indicates the body is experiencing tissue damage and inflammation. Pain can be managed with analgesics. One of the plants that is thought to have an analgesic effect is matoa leaf (Pometia pinnata J.R. Forst & G. Forst). This study was an experimental study using male white mice which were divided into 5 treatment groups, namely group I was given NaCMC as a negative control, group II was given ibuprofen as a positive control, and groups III, IV, and V were given EEDM with a successive dose of 200 mg /kgBB, 400 mg/kgBB, and 800 mg/kgBB. The test animals were induced with 1% acetic acid intraperitoneally after 30 minutes of oral administration of the test preparation. Observations were made by calculating the pain response marked by stretching for 180 minutes with an interval of 10 minutes. The research data were processed statistically using the One Way ANOVA test and the LSD follow-up test. The positive control group for the EEDM group at doses of 200 mg/kg, 400 mg/kg, and 800 mg/kg showed no significantly different results with a P>0,05. From the study results, it can be concluded that EEDM has an analgesic effect on male white mice with an effective dose of 800 mg/kgBB.